THE STATE OF HEALTH OF ADOLESCENTS WITH INFANTILE CEREBRAL PARALYSIS: MORBIDITY ACCORDING TO THE DATA OF PROFOUND EXAMINATION - Z.M. Aminova; S.Sh. Yafarova; S.Ya. Volgina ("Paediatrician" Publishers LLC, 2009)
(Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(3):139-140)